Stevens–Johnson syndrome and toxic epidermal necrolysis: a systematic review and meta-analysis. (2nd December 2021) - Houschyar, Khosrow S; Tapking, Christian; Borrelli, Mimi R; Puladi, Behrus; Ooms, Mark; Wallner, Christoph; Duscher, Dominik; Pförringer, Dominik; Rein, Susanne; Reumuth, Georg; Schulz, Torsten; Nietzschmann, Ina; et al.
Abstract : Objective: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare and severe skin and mucosal reactions that are associated with high mortality. Despite the severity, an evidence-based treatment protocol for SJS/TEN is still lacking. Method: In this systematic review and meta-analysis, the PubMed database was searched using the following terms: [Stevens–Johnson syndrome] OR [toxic epidermal necrolysis] AND [therapy] OR [treatment] over a 20-year period (1999–2019) in the German and English language. All clinical studies reporting on the treatment of SJS/TEN were included, and epidemiological and diagnostic aspects of treatment were analysed. A meta-analysis was conducted on all comparative clinical studies that met the inclusion criteria. Results: A total of 88 studies met the inclusion criteria, reporting outcomes in 2647 patients. Treatment was either supportive or used systemic corticosteroid, intravenous immunoglobulin, plasmapheresis, cyclosporine, thalidomide or cyclophosphamide therapy. The meta-analysis included 16 (18%) studies, reporting outcomes in 976 (37%) patients. Systemic glucocorticoids showed a survival benefit for SJS/TEN patients in all analyses compared with other forms of treatment. Cyclosporine treatment also showed promising results, despite being used in a small cohort of patients. No beneficial effects on mortality could be demonstrated for intravenous immunoglobulins. Conclusion: Glucocorticoids and cyclosporine may be tentatively recommended as the most promising immunomodulatory therapies for SJS/TEN, but these results should be investigated in future prospective controlled trials.